Structure and function role of soil nematode communities in different types of vegetation in Yogyakarta and Central Java, Indonesia - SIWI INDARTI; SRI NURYANI HIDAYAH UTAMI; NUGROHO SUSETYA PUTRA; RINA MAHARANI (Society for Indonesian Biodiversity, 2024)
Abstract. Indarti S, Utami SNH, Putra NS, Maharani R. 2024. Structure and function role of soil nematode communities in different types of vegetation in Yogyakarta and Central Java, Indonesia. Biodiversitas 25: 2765-2772. Soil nematodes are crucial parts of the soil organism community and play a significant role in many ecological soil processes. It is necessary to pay greater attention to the lack of knowledge regarding the composition and role of the soil nematode community in different vegetations. Hence, the nematode structure community from minimal to soil stillages have been observed and compared from seven distinct types of vegetation. This study aimed to determine the soil nematode community structure, which includes the dominance, abundance, richness, diversity, and functional role of nematodes, as well as other chemical soil properties. Vegetation type represents soil management and has an impact on the life of soil organisms such as nematodes. A total of approximately 2328 soil nematodes were found, and 18 genera were identified. The Nematode Indicator Joint Analysis (NINJA) revealed that the vegetation type, land use, and soil chemical properties influence the nematode’s abundance, dominance, and structure differently. Through those results, the authors confirmed that soil nematodes in cultivated vegetation are dominated by the trophic groups of plant-parasitic nematodes and bacterivores. Conversely, predator, omnivores, and fungivores nematodes dominate in soil with minimal tillage. Overall, this study highlights the importance of soil nematode analysis in sustainable agricultural soil ecosystems.